Fast determination of fipronil and its metabolites in seafood using PRiME pass-through cleanup followed by isotope dilution UHPLC-MS/MS. Issue 15 (6th April 2018) - Zhang, Yun; Zhao, Yong-Gang; Cheng, He-Li; Muhammad, Nadeem; Chen, Wei-Sheng; Zeng, Xiu-Qiong; Zhu, Yan
Abstract : A simple and effective method based on the PRiME pass-through cleanup procedure followed by UHPLC-MS/MS was developed for analyzing fipronil and its metabolites in seafoods. Abstract : A simple and effective method based on the PRiME (process, robustness, improvements, matrix effects, ease of use) pass-through cleanup procedure followed by ultra-high performance liquid chromatography-tandem quadrupole mass spectrometry (UHPLC-MS/MS) was developed for analyzing fipronil and its metabolites in seafoods. Matrix effects in seafoods were effectively improved. Validation results demonstrated that this method was suitable for monitoring fipronil residues in seafoods.